Red and roe deer densities and distribution in Northeastern Portugal - Valente, Ana Margarida dos Santos (2015)
Monitoring ungulates is a major challenge to perform management strategies, either back in the 70’s to enable their conservation that lead to their great recovery, as to manage their actual expansion. Their current wide range distribution and high den-sities across Europe promotes damages in ecosystems that need to be handled based on scientific knowledge. In Portugal ungulate monitoring and ecology is still in an early stage, however efforts have been made to gather valid information on north-eastern ungulate populations. In this work density of red and roe deer were estimated coupling line transects to perform pellet group counts with a distance sampling ap-proach. The density of red deer estimated for Montesinho Natural Park (MNP) was 3.05 ind./100 ha (95% CI: 2.05 – 4.54), splitted in two sub-areas: Serra de Mon-tesinho (SM) with 1.23 ind./100 ha and Lombada National Hunting Area (LNHA) with 5.23 ind./100 ha. Roe deer densities were estimated with recourse to a spatial methodology recently developed, the Density Surface Models (DSMs – with a dis-tance sampling framework), which enables the assessment of the relationships be-tween animal’s density and spatial variables selected according to species ecological requirements. As well roe deer densities were estimated for MNP and Serra da Nogueira (SN) with a global density of 3.01 ind./100 ha (95% CI: 2.34 – 3.87): SM with 3.74 ind./100 ha, LNHA with 1.59 ind./100 ha and SN with 3.62 ind./100ha. Furthermore this approach enables the drawing of an abundance distribution map across the study area, especially useful when communicating results to wildlife man-agers. Roe deer densities showed to increase as distance to roads increased, while surprisingly shown an increase as distance to human populations decreased. As ex-pected, cover areas shown its importance for roe deer, a prey species for Iberian wolf. The spatial analysis confirmed that DSMs represent a good approach to estimate ungulate densities, and should be encouraged in future works. Future studies are mandatory to assess red and roe deer ecological requirements and evaluate trends over the years, in order to stablish management plans to handle the damages caused by these species.